Nutritional quality and ruminal degradability of banana (Musa AAA) plant. - Chacón-Hernández, Pablo (2016)
The objective of the study was to evaluate the nutritional value of a Musa AAA fodder bank. The study was conducted at the Alfredo Volio Mata Experimental Station of the University of Costa Rica. It took place from May to November 2013 using a complete random block design. Mean values for the whole plant were of 5.67% of dry matter, 6.50% of crude protein, 53.91% of neutral detergent fiber, 35.67% of acid detergent fiber, 7.61% of lignin, 28.07% of cellulose, 18.23% of hemicellulose, 1.95% of ether extract, 19,30% of ash, 4.63% of crude protein attached to the neutral detergent fiber, and 25.32% of non- fibrous carbohydrates. Besides, statistical differences were found (p<0.05) for all bromatological components, according to the sampled plant part. The analysis of ruminal degradability showed values ranging from 18.38% to 47.43% for the soluble fraction, from 33.45% to 45.76% for the degradable fraction, from 1.65%/h to 7.51%/h for the degradation speed, and from 64.14% to 82.86% the potentially degradable percentage, depending on the part of the plant sampled. According to analyzed data, Musa AAA plants could be used for feeding ruminants where available.